2021
DOI: 10.1108/maj-09-2020-2845
|View full text |Cite
|
Sign up to set email alerts
|

Upward feedback falling on deaf ears: the effect on provider organizational citizenship and counterproductive work behaviors in the audit profession

Abstract: Purpose The purpose of this paper is to explore how firms can enhance feedback systems by studying the effects of offering junior auditors an opportunity to provide upward feedback and acknowledging their voice has been heard and will be considered for evaluation purposes. Design/methodology/approach This study uses a 2 × 1 + 1 (voice confirmation × opportunity + no opportunity) between-subjects experimental design that manipulated upward feedback opportunity (i.e., opportunity or no opportunity) and voice c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
(68 reference statements)
1
4
0
Order By: Relevance
“…As previously noted, we also included "þ2" no opportunity cells to understand auditor perceptions of justice, support and turnover when auditors do not have the opportunity to provide upward feedback. We expect results similar to those of Vagner et al (2022), who find that college students perceive the opportunity to provide feedback as fairer than having no opportunity to do so. Participants were split into either the favorable or unfavorable supervisor experience condition.…”
Section: Additional Analysessupporting
confidence: 56%
See 1 more Smart Citation
“…As previously noted, we also included "þ2" no opportunity cells to understand auditor perceptions of justice, support and turnover when auditors do not have the opportunity to provide upward feedback. We expect results similar to those of Vagner et al (2022), who find that college students perceive the opportunity to provide feedback as fairer than having no opportunity to do so. Participants were split into either the favorable or unfavorable supervisor experience condition.…”
Section: Additional Analysessupporting
confidence: 56%
“…These factors are also highlighted in Erdogan’s (2002) model of procedural justice, which suggests that environmental features such as the perceived fairness of the process, superior–subordinate interactions and organizational culture affect the likelihood of an effective upward feedback culture. Supporting these theories, Vagner et al. (2022) find that accounting students perceive the opportunity to provide upward feedback as fairer than having no opportunity to do so.…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 58%
“…, 2021; Griffin and Lopez, 2005; Renn et al ., 2005). Early research often used terms like counterproductive work behaviours (Vagner et al. , 2022; Fox et al.…”
Section: Introductionmentioning
confidence: 99%
“…Given the widespread acceptance of the definition of workplace deviance by Robinson and Bennett (1995) as a violation of formal organisational rules, extant research has primarily considered deviant behaviour to be self-interested or unethical (De Clercq et al, 2021;Griffin and Lopez, 2005;Renn et al, 2005). Early research often used terms like counterproductive work behaviours (Vagner et al, 2022;Fox et al, 2001), dysfunctional behaviour (Griffin et al, 1998), and non-complaint work behaviour (Puffer, 1987) etc. to describe and study workplace deviance.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that organizations benefit from employee contributions that go above and beyond the formal job requirements, also known as OCB ( Organ, 2018 ). Scholars strive to explain the positive effects of OCB from a broader research perspective ( Vagner et al, 2022 ). For instance, OCB presents commitments that reasonable in nature and when totaled after some time and people, may upgrade the execution by greasing up the building the mental texture of the association, decreasing erosion, and/or expanding productivity ( Guntuku et al, 2020 ).…”
Section: Impact On the Organizationmentioning
confidence: 99%